2021
DOI: 10.1111/btp.13051
|View full text |Cite
|
Sign up to set email alerts
|

Elevational distribution of birds in an Eastern African montane environment as governed by temperature, precipitation, and habitat availability

Abstract: Tropical species, many of which have limited thermal tolerances and narrow ecological niches, are likely to experience elevational shifts due to climate change. However, our ability to predict these shifts is limited by a scarcity of baseline data on current distributions and a lack of understanding of drivers of species ranges. To characterize the elevational distributions of a suite of Afromontane birds, we conducted annual point counts between 2013 and 2018 at 297 plots across habitats and elevations (2416–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…The particularly high prevalence of excavated cavities in branches may be related to excavators' preferences for softer wood for excavation of cavities (Schepps et al, 1999), though follow‐up studies would need to confirm that branches differ from trunks in wood tissue hardness. With regards to orientation, we find that most trees in our study area grow on slopes that face a southern or eastern exposure, and high decay‐inducing levels of precipitation and moisture may be reached on the northwestern slope‐facing sides of trees as precipitation increases with elevation (van der Hoek et al, 2021). Following this, we may also assume that excavated cavities are predominantly found on the northwestern side of trees where the relatively softer wood would be easier to excavate.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The particularly high prevalence of excavated cavities in branches may be related to excavators' preferences for softer wood for excavation of cavities (Schepps et al, 1999), though follow‐up studies would need to confirm that branches differ from trunks in wood tissue hardness. With regards to orientation, we find that most trees in our study area grow on slopes that face a southern or eastern exposure, and high decay‐inducing levels of precipitation and moisture may be reached on the northwestern slope‐facing sides of trees as precipitation increases with elevation (van der Hoek et al, 2021). Following this, we may also assume that excavated cavities are predominantly found on the northwestern side of trees where the relatively softer wood would be easier to excavate.…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, our estimate of 134.7 trees per hectare is well below the interquartile range of tree densities for either tropical moist or dry forest (lower quartile cut‐off >250 trees per hectare for either forest type, Crowther et al, 2015). In addition, but related to low tree availability at high elevations near the treeline ecotone, there is a potentially low abundance and richness of excavators (avifauna) in VNP (van der Hoek et al, 2021; van der Hoek, Faida, et al, 2020; van der Hoek, Gaona, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with the estimated reduction in residual pairwise correlations in the extended warbler model ( figure 4 ), these results provide strong evidence of niche partitioning along this Grinellian mechanism for ecologically similar bird species in the Virunga volcanoes, consistent with previous studies in the Cameroonian mountains [ 61 ], Himalayan highlands [ 26 ], tropical Andes [ 62 , 63 ] and in New Guinea highlands [ 64 , 65 ]. A recent survey of birds covering a third of the study area (Parc National des Volcans in Rwanda) identified 57% of species to be associated with narrow elevation bands (less than 300 m; [ 66 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Female availability naturally varies as a result of variation in the environment. Changes in abiotic factors, such as precipitation and temperature, often moderate habitat complexity, resource availability and movement between populations (Ferger et al 2014; van der Hoek et al 2022), altering mate encounter rates and the adult sex ratio. A classic example is the approach of spring, coinciding with longer days, higher temperatures and more food, which triggers increased conspecific interactions and reproductive activities (Kahn et al 2013; De Marchi et al 2015).…”
Section: Introductionmentioning
confidence: 99%